Hydrogen sulfide suppresses the expression of MMP-8, MMP-13, and TIMP-1 in left ventricles of rats with cardiac volume overload - Zhang Chao-ying; Li Xiao-hui; Zhang Ting; Fu Jin; Cui Xiao-dai (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of hydrogen sulfide (H2S) on the left ventricular expression of MMP-8, MMP-13, and TIMP-1 in a rat model of congenital heart disease. Methods: Male SD rats underwent abdominal aorta-inferior vena cava shunt operation. H2S donor NaHS (56 μmol·kg−1·d−1, ip) was injected from the next day for 8 weeks. At 8 weeks, the hemodynamic parameters, including the left ventricular systolic pressure (LVSP), the left ventricular peak rate of contraction and relaxation (LV±dp/dtmax) and the left ventricular end diastolic pressure (LVEDP) were measured. The left ventricular tissues were dissected out, and hydroxyproline and collagen I contents were detected with ELISA. The expression of MMP-8, MMP-13, and a tissue inhibitor of metalloproteinase-1 (TIMP-1) in the tissues was measured using real-time PCR, Western blotting, and immunohistochemistry, respectively. Results: The shunt operation markedly reduced LVSP and LV±dp/dtmax, increased LVEDP, hydroxyproline and collagen I contents, as well as the mRNA and protein levels of MMP-8, MMP-13, and TIMP-1 in the left ventricles. Chronic treatment of the shunt operation rats with NaHS effectively prevented the abnormalities in the hemodynamic parameters, hydroxyproline and collagen I contents, and the mRNA and protein levels of MMP-13 and TIMP-1 in the left ventricles. NaHS also prevented the increase of MMP-8 protein expression, but did not affect the increase of mRNA level of MMP-8 in the shunt operation rats. Conclusion: H2S suppresses protein and mRNA expression of MMP-8, MMP-13, and TIMP-1 in rats with cardiac volume overload, which may be contributed to the amelioration of ventricular structural remodeling and cardiac function.